2019
DOI: 10.1016/j.cnur.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Infectious Diseases

Abstract: KEYWORDSEmerging infections Zoonotic diseases Vector-borne diseases Candida auris Elizabethkingia anopheles Avian influenza mcr-1 KEY POINTSMost emerging infectious diseases (EID) are caused by zoonotic pathogens.Vector-borne diseases are a major public health problem in the United States.Factors contributing to EID include population growth, spread in health care facilities, aging population, global travel, and changing vector habitats related to climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 22 publications
2
99
0
3
Order By: Relevance
“…Over the past three and half decades at least 30 new infectious agents affecting humans have emerged including SARS-CoV-2, and most of them are zoonotic. It was also reported that 61 % infectious organisms affecting humans are zoonotic diseases which can infect both human and animals (Nii-Trebi, 2017;McArthur, 2019). Previous studies have revealed that both SARS-CoV-1 and MERS-CoV originated in bats (Lau et al, 2010;Guan et al, 2003;Lau et al, 2005;Li et al, 2005), with SARS-CoV-1 jumping to humans from palm civets (Song et al, 2005;Chinese, 2004;Wang et al, 2005) and MERS-CoV jumping to humans from camels (Muller et al, 2014;Chu et al, 2014) following intermediate transmission from bats (Lau et al, 2010;Guan et al, 2003;Lau et al, 2005;Li et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past three and half decades at least 30 new infectious agents affecting humans have emerged including SARS-CoV-2, and most of them are zoonotic. It was also reported that 61 % infectious organisms affecting humans are zoonotic diseases which can infect both human and animals (Nii-Trebi, 2017;McArthur, 2019). Previous studies have revealed that both SARS-CoV-1 and MERS-CoV originated in bats (Lau et al, 2010;Guan et al, 2003;Lau et al, 2005;Li et al, 2005), with SARS-CoV-1 jumping to humans from palm civets (Song et al, 2005;Chinese, 2004;Wang et al, 2005) and MERS-CoV jumping to humans from camels (Muller et al, 2014;Chu et al, 2014) following intermediate transmission from bats (Lau et al, 2010;Guan et al, 2003;Lau et al, 2005;Li et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of zoonotic diseases increases when humans live in close contact with animals, such as when both hosts overlap in a geographic region [117]. Thus, it is important to consider humans together with animals and the environment as a whole, which is emphasized in the One Health Strategy, in order to prevent and control the emergence of zoonotic diseases.…”
Section: Does Onchocerciasis Have a Zoonotic Character?mentioning
confidence: 99%
“…Thus, it is important to consider humans together with animals and the environment as a whole, which is emphasized in the One Health Strategy, in order to prevent and control the emergence of zoonotic diseases. Emerging zoonotic diseases impact on public health and socioeconomic aspects of the global population [117].…”
Section: Does Onchocerciasis Have a Zoonotic Character?mentioning
confidence: 99%
“…Virus transmission is performed by mosquito vector, with predominance of the genus Aedes (Bhatt et al, 2013). Like other emerging infectious diseases, outbreaks of the DENV are unpredictable and potentially widespread, and can result in epidemics that threaten global public health (Fauci and Morens, 2012;Morens and Fauci, 2013;McArthur, 2019). The disease is endemic in over 120 countries, which account for 3.9 billion people at risk of infection worldwide (World Health Organization, 2020).…”
Section: Introductionmentioning
confidence: 99%